The Difference Of The Results Of Tests To Diagnose VCT Counselor ln The Examination Of HIV In Public Health Office Turen - Sasono, Tri Nurhudi (Journal of Global Research in Public Health, 2017)
A person's HIV-positive status can only be proven by a voluntary blood test conducted by VCT (Voluntary Counseling and Testing). Communities can only know if PLWHA discloses HIV positive status to counselor with confidentiality. VCT is a major component in HIV / AIDS prevention programs, will now VCT has not been a great strategy in developing countries including Indonesia in particular. Voluntary enthusiasm factors have been the determinants of the current low VCT visits, and the diversity of results to diagnose HIV-infected HIV-AIDS is still â€œtabuâ€ and disgrace of condemnation by society is also one of the supporting factors. The purpose of this study was to determine differences in the conformity of the results of the examination of counselors in VCT examination to diagnose HIV. The research design uses categorical comparative analysis with sampling technique using purposive sampling. The number of research subjects consisted of 4 counselors who were in Puskesmas Turen. The results of the study by comparing the results of interviews and observations between VCT counselors. Based on the test results with Kappa test, the value of Kappa coefficient = 0.39 means that the agreement observed by the counselor between 39% between the perfect agreement. The conclusion in this research is the suitability of kappa test result among VCT counselor examination. The nursing implication in this research is that counselors are expected to verify data verification and validation of other counselor checkers to ensure a predetermined HIV diagnosis.